The beneficial roles of metformin on the brain with cerebral ischaemia/reperfusion injury - Tom Leech (2019)
© 2019 Elsevier Ltd Cerebral ischaemia/reperfusion (I/R) injury is the transient loss, followed by rapid return, of blood flow to the brain. This condition is often caused by strokes and heart attacks. The underlying mechanisms resulting in brain damage during cerebral I/R injury include mitochondrial dysregulation, increased oxidative stress/reactive oxygen species, blood-brain-barrier breakdown, inflammation of the brain, and increased neuronal apoptosis. Metformin is the first-line antidiabetic drug which has recently been shown to be capable of acting through the aforementioned pathways to improve recovery following cerebral I/R injury. However, some studies have suggested that metformin therapy may have no effect or even worsen recovery following cerebral I/R injury. The present review will compile and examine the available in vivo, in vitro, and clinical data concerning the neuroprotective effects of metformin following cerebral I/R injury. Any contradictory evidence will also be assessed and presented to determine the actual effectiveness of metformin treatment in stroke recovery.